The God Who Believes: Faith, Doubt, and the Vicarious Humanity of Christ – Christian D. Kettler - Schweitzer, William (Reviews in religion and theology, 2006)
Book reviewed: The God Who Believes: Faith, Doubt, and the Vicarious Humanity of Christ, Christian D. Kettler, Cascade 2005 (1-59752-188-4), xiv + 194 pp., pb $24.00